?ACUTE TOXICITY OF COPPER, CADMIUM AND COPPER -CADMIUM MIXTURE TO THE LARVAE OF THE SHRIMP PENAEUS MONODON (Biological Sciences - PJSIR, 1996)
Lethal concentration (LC)ofcopper forPenaeus monodon at variousstages ofits lifecycle wasobserved. Itwas 300 ~glL for nauplii while 100% mortality was observed for zoea I, Zoea II, Zoea III and Mysist I. 95.3% and 30.0% mortality was for Mysis III and postlarval stages respectively. The lethal concentration (LC) of cadmium for nauplii, zoea I, ZII, Zlll, Mysis I, Mysis III and postiarvae were between 50-250 ug/L, In mixture these values were found to be between II 0-200~glL.